2016
DOI: 10.3857/roj.2016.01795
|View full text |Cite
|
Sign up to set email alerts
|

The impact of radiotherapy on clinical outcomes in parameningeal rhabdomyosarcoma

Abstract: PurposeRadiotherapy (RT) is considered a mainstay of treatment in parameningeal rhabdomyosarcoma (PM-RMS). We aim to determine the treatment outcomes and prognostic factors for PM-RMS patients who treated with RT. In addition, we tried to evaluate the adequate dose and timing of RT.Materials and MethodsTwenty-two patients with PM-RMS from 1995 to 2013 were evaluated. Seven patients had intracranial extension (ICE) and 17 patients had skull base bony erosion (SBBE). Five patients showed distant metastases at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Radiotherapy has been confirmed to significantly increase local control for patients with sinonasal RMS and non-RMS [ 18 , 19 ]. For non-RMS, Lucyna et al found that the radiation dose had a considerable effect on the treatment outcome: a 1-Gy increase in the dose delivered decreased the risk of death and local failure by 3%.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy has been confirmed to significantly increase local control for patients with sinonasal RMS and non-RMS [ 18 , 19 ]. For non-RMS, Lucyna et al found that the radiation dose had a considerable effect on the treatment outcome: a 1-Gy increase in the dose delivered decreased the risk of death and local failure by 3%.…”
Section: Discussionmentioning
confidence: 99%